Fourier‐based decomposition for simultaneous 2‐voxel MRS acquisition with 2SPECIAL. Issue 5 (30th July 2022) - Riemann, Layla Tabea; Aigner, Christoph Stefan; Mekle, Ralf; Speck, Oliver; Rose, Georg; Ittermann, Bernd; Schmitter, Sebastian; Fillmer, Ariane
Abstract : Purpose: To simultaneously acquire spectroscopic signals from two MRS voxels using a multi‐banded 2 spin‐echo, full‐intensity acquired localized (2SPECIAL) sequence, and to decompose the signal to their respective regions by a novel voxel‐GRAPPA (vGRAPPA) decomposition approach for in vivo brain applications at 7 T. Methods: A wideband, uniform rate, smooth truncation (WURST) multi‐banded pulse was incorporated into SPECIAL to implement 2SPECIAL for simultaneous multi‐voxel spectroscopy (sMVS). To decompose the acquired data, the voxel‐GRAPPA decomposition algorithm is introduced, and its performance is compared to the SENSE‐based decomposition. Furthermore, the limitations of two‐voxel excitation concerning the multi‐banded adiabatic inversion pulse, as well as of the combined B0 shim and B1 + adjustments, are evaluated. Results: It was successfully shown that the 2SPECIAL sequence enables sMVS without a significant loss in SNR while reducing the total scan time by 21.6% compared to two consecutive acquisitions. The proposed voxel‐GRAPPA algorithm properly reassigns the signal components to their respective origin region and shows no significant differences to the well‐established SENSE‐based algorithm in terms of leakage (both <10%) or Cramér‐Rao lower bounds (CRLB) for in vivo applications, while not requiring the acquisition of additional sensitivity maps and thus decreasing motion sensitivity. Conclusion: The use of 2SPECIAL in combination with the novel voxel‐GRAPPA decomposition technique allows a substantial reduction of measurement time compared to the consecutive acquisition of two single voxels without a significant decrease in spectral quality or metabolite quantification accuracy and thus provides a new option for multiple‐voxel applications.